Nove lincidence matrix differential power analysis for resisting ghost peak - Zijing JIANG; Qun DING (Tongxin xuebao)
At present, differential power analysis (DPA) is one of the most important threats to the security of block ciphers in chips.When the collected power trace is insufficient, DPA is vulnerable to ghost peak caused by the difference mean value generated by the wrong key.Based on DPA, a incidence matrix differential power analysis (IMDPA) was proposed which could effectively resist ghost peak.The prediction difference mean matrix was constructed to avoid the influence of the non leaking interval on the key guessing of the leaking interval by using the weak correlation of the guessing key in the non leaking interval.The proposed IMDPA was tested in different leak intervals of AES-128 algorithm.The results show that compared with traditional DPA, IMDPA requires less (up to 85%) power trace to guess the correct key.At the same time, the key guessing efficiency of AES-128 under the implementation of protective measures by IMDPA still has obvious advantages.In order to further verify the universality of IMDPA in block ciphers, experimental verification is conducted on SM4 algorithm.Compared with traditional DPA, IMDPA requires less (up to 87.5%) power traces to guess the correct key.